The movementist grammar during the left turn: The case of Argentina - Natalucci, Ana (Revista de Sociología, 2018)
During the left turn in Argentina, one of the notable changes that took place concerned the articulatory capacity of the government. This change was expressed through the re-creation of movementist grammar and occurred alongside the formation of a political movement that involved social and union organizations and the elite. The objective of the present article is to analyze political articulation in the context of the formation and consolidation of relationships between Kirchnerism and such organizations. The central assertion is that this grammar began to develop in 2003, constituted a standard in the discourse between 2007 and 2010, and has since fallen into disuse. The organizations and the elite implemented a number of strategic and programmatic agreements, but given the focus of these on concentration of power, movementist grammar suffered from low levels of institutionalization. The present article brings together the conclusions of an international project which sought to analyze the end of the left turn in Latin America.